Assessment of knowledge, attitude and practices of tobacco cessation counselling and nicotine replacement therapy among dental professionals - Anagha V. Shete; Mrinal V. Shete; Ashwini Nerkar Rajbhoj; Ladusingh Rajpurohit; Arti Hajarnavis; Abhijeet Sande (Journal of Family Medicine and Primary Care)
Background: Establishment of Tobacco Cessation Centres across all dental institutions has been made mandatory by the Dental Council of India. To make it a success, adequate knowledge and training, positive attitude and practices are expected by the dental health care professionals. Our study aims to assess the knowledge, attitude and practices of dentists towards Tobacco Cessation Counselling (TCC) and Nicotine Replacement Therapy (NRT). Materials and Methods: 200 participants (60 faculty members, 20 postgraduate students and 120 interns) participated in this cross-sectional study. A self-designed questionnaire of 27 questions was used to assess the knowledge, attitude and practices of the participants regarding TCC and NRT. A descriptive analysis of the data was done. Frequency and percentage were calculated for each variable. The data were processed and analysed using SPSS software version 19-SPSS Inc. Chicago, IL, USA. Results: 22% candidates were trained for TCC as opposed to 78% candidates who didn’t have an idea about it. 65% participants knew about various agents which are used for NRT but many did not know how to prescribe them. 83.5% were not willing to spare time for tobacco cessation in their private practice. Only 12% were currently practising TCC or NRT at workplace. Conclusion: Inclusion of TCC in the undergraduate curriculum, training and updating of dental faculty and students regarding TCC and NRT will help in serving the noble cause.